Dynamic fatigue reliability analysis of wheel hub drive system for electric drive mining dump truck - YANG HaoDong; YAN ChangFeng; XIE HePing; KANG JianXiong; ZHANG Ke (Jixie qiangdu)
Aiming at the problem that the reliability of the hub drive system under the actual load could not be accurately evaluated at the design stage, a method for evaluating reliability which applied in the design stage was proposed. The dynamic fatigue reliability of each gear pair of the hub drive system was calculated by replacing the actual random load with the static load of the rated design load in the method. The fatigue damage and reliability of each gear pair of the wheel hub drive system under the actual load were simulated through Romax Design software, and the feasibility of the method d was verified, which could provide theoretical basis and practical test guidance for the reliability design of wheel drive system.